HUBUNGAN PENGETAHUAN DAN MOTIVASI IBU TERHADAPPEMBERIAN IMUNISASI DASAR LENGKAP PADA BAYI 12-24 BULAN DI PUSKESMAS TALANG BANJAR KOTA JAMBI - Devi Ayu Resia (STIKES Keluarga Bunda Jambi, 2019)
It is estimated that throughout the world in 2013, around 21.8 million children who did not get immunization, which could save their lives. Of the 20 puskesmas in Jambi City, the complete coverage of basic immunization data that did not meet the target was the Talang Banjar Health Center.This study is a cross sectional analytic study. The population of this study were all 12-24 month infants in Talang Banjar Health Center, Jambi City in 2019. The sample in this study were 33 people taken by simple random sampling technique. This research was conducted at Talang Banjar Health Center, Jambi City in April-May 2019. Data were analyzed by univariate and bivariate using the chi square test. The results showed that most respondents had enough knowledge as many as 16 respondents (48.5%), high motivation as many as 20 respondents (60.6%) and complete basic immunization as many as 18 respondents (54.5%). There is a relationship between mother's knowledge (p value = 0.005) and mother's motivation (p value = 0.010) with complete basic immunization because the p-value is <0.05. It can be concluded that maternal knowledge and motivation influence the provision of complete basic immunization in infants 12-24 months. For this reason, health workers need to improve the provision of information on the health of infants and toddlers, especially in providing complete basic immunization.